2013
DOI: 10.1080/13691058.2013.809478
|View full text |Cite
|
Sign up to set email alerts
|

When ‘raw sex’ turns to a ‘raw deal’ … taking the opportunity to think about sex? Interviews with HIV-positive gay men diagnosed with acute hepatitis C

Abstract: Since 2001, cases of hepatitis C virus (HCV) sexual transmission have been reported in France, among HIV-positive gay men who do not inject drugs. An earlier study focused on the incidence of acute hepatitis C and risk factors associated with HCV transmission. The present study, based on in-depth interviews, aimed to highlight the biography, the sexual practices and the experiences of gay men infected with HCV. Beyond an apparent uniformity, the group of interviewees illustrates a variety of situations, life s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
9
1
2
Order By: Relevance
“…The results obtained confirm those of qualitative7 8 and quantitative9 studies previously conducted in France in smaller samples.…”
Section: Discussionsupporting
confidence: 89%
“…The results obtained confirm those of qualitative7 8 and quantitative9 studies previously conducted in France in smaller samples.…”
Section: Discussionsupporting
confidence: 89%
“…Studies reported that some patients were shocked or surprised by their HCV diagnosis [23, 25, 33, 34, 36, 40, 43, 44, 51, 52, 60, 63], while others were not surprised or had expected a positive HCV result [23, 33, 36, 38]. Those who were not shocked or surprised at the time of diagnosis were often current IDUs who viewed contracting HCV as inevitable [22, 23, 25, 36, 38], often thinking of HCV as a “legacy of drug use…the junky flu, that's one of the by-products” [40].…”
Section: Resultsmentioning
confidence: 99%
“…transmitted HCV (12)(13)(14)(15), which would also explain the recently reported increasing number of re-infections with HCV after successful clearance or treatment of the first episode (16). Taken together, both patient groups continue to see new cases of HCV infection either on the basis of absent changes in behavioural patterns or missing needle exchange programs.…”
mentioning
confidence: 95%
“…Among the first, several outbreaks of acute HCV infection have been described in Australia, Europe and North America over the last decade . Studies have suggested that these outbreaks are explained by an increase in sexually transmitted HCV , which would also explain the recently reported increasing number of re‐infections with HCV after successful clearance or treatment of the first episode . Taken together, both patient groups continue to see new cases of HCV infection either on the basis of absent changes in behavioural patterns or missing needle exchange programs.…”
mentioning
confidence: 99%